Vladimir Putin dan Dekonstruksi Soft Power Rusia - alfarauqi, Mohamad dziqie aulia (Jurnal Hubungan Internasional, 2017)
Vladimir Putin is a figure behind Russian intelligence after the collapse of the Soviet Union. Putin proved to be able to instill political and economic stability in the country and be able to stay on the peak of Russia's leadership for more than 15 years. One feature of Russia's foreign policy is the control of mass media and propaganda that gives Putin the power of public opinion. This condition is known as Russian soft power. This paper argues that Russia has made a deconstruction of its concept of soft power. Using the Postmodernism perspective, this paper seeks to see the deconstruction of soft power concept by Vladimir Putin. The conclusion of this research is in Putin's position of practicing the concept of soft power with a different style from the concept of soft power by Joseph Nye. He saw that the concept of soft power should be detached from the hegemony of United State and the west and must be in line with the national security of Russia so that it has implications for the policy against US hegemony